Kinetics of Circulating MicroRNAs in Response to Cardiac Stress in Patients With Coronary Artery Disease. Issue 8 (27th July 2017) - Jansen, Felix; Schäfer, Lisa; Wang, Han; Schmitz, Theresa; Flender, Anna; Schueler, Robert; Hammerstingl, Christoph; Nickenig, Georg; Sinning, Jan‐Malte; Werner, Nikos
Abstract : Background: Circulating microRNAs (miRNAs/miRs) are regulated in patients with coronary artery disease. The impact of transient coronary ischemia on circulating miRNA levels is unknown. We aimed to investigate circulating miRNA kinetics in response to cardiac stress in patients with or without significant coronary stenosis. Methods and Results: Eighty of 105 screened patients with stable coronary artery disease underwent dobutamine stress echocardiography before coronary angiography. Nine circulating vascular miRNAs (miRNA‐21, miRNA‐26, miRNA‐27a, miRNA‐92a, miRNA‐126‐3p, miRNA‐133a, miRNA‐222, miRNA‐223, and miRNA‐199‐5p) were quantified in plasma by reverse transcription polymerase chain reaction before, immediately after, and 4 and 24 hours after dobutamine stress echocardiography. Quantitative polymerase chain reaction revealed increased miRNA‐21, miRNA‐126‐3p, and miRNA‐222 levels at 24 hours after dobutamine stress echocardiography in all patients. On coronary angiography, significant coronary artery stenoses (>80% diameter stenosis) were found in 41 patients. Stratifying patients according to the prevalence of significant stenoses, patients with stenosis showed an increase of circulating miRNA‐21, miRNA‐126‐3p, and miRNA‐222 in response to cardiac stress. In patients without significant stenoses (<50% diameter stenosis), miRNA‐92a levels gradually increased in response to cardiac stress. Conclusions: miRNAs are distinctly released into the circulation in response to cardiac stress depending on the prevalence of significant coronary stenoses.